Al-Khasais al-Islamiyah fi shakhsiyah al-mar'ah al-Malayuwiyah fi al-hikayat al-Malayuwiyah al-qadimah: dirasah adabiyah tahliliyyah = Islamic values in the characteristics of Malay woman in classical Malay texts: a literary analysis - Abd Rahim, Nadiah; Ahmad H.Osman, Rahmah; Abd Manap, Nur Fazlina (Al Hikmah Research and Publication Centre., 2022)
Every race in the world is characterized by a special culture that generates an individual's personality. Malay emphasizes the culture and customs of all society, especially women, but there are many social problems among women in this era because of the lack of adherence to religion and adherence to Malay customs. According to this research, ancient Malay tales are neglected or forgotten and its texts are unknown to present generations. Therefore, the research aims to discover the Islamic characteristics found in Malay women's characters in selected ancient Malay tales such as from the Poem of Siti Zubaydah, the tale of Hang Tuah, the masterpiece of the Melaka, the tale of the kings of Pasai and the dynasty of the sultans with their characteristics and examples. This research is based on the analytical approach in literature by reviewing some related references and books in the Malay language. This research has found seven Islamic characteristics in the characters of Malay women from the selected tales, such as patience and strength, the religious characteristic of women, the characteristic of a woman's loyalty to her husband, the characteristic of a woman's purity, the characteristic of mother's love and sympathy, the characteristic of independent women, and the characteristic of women's leadership.